The influence of el nino and la nina on rainfall data of east lampung regency, lampung province - Gani, Rama Dian; Zakaria, Ahmad; Kusumastuti, Dyah Indriana (Universitas Lampung, 2021)
This research was conducted to determine the impact of the areas where El Nino and La Nina were the most dominant. The data used in this study are daily rainfall data in 5 rain stations located in East Lampung. Data length from 1989 to 2018 at each station, this data was taken from the Mesuji River Basin - Sekampung (BBWSMS). This modeling is carried out using a data length of 30 years for a data term of 10957.By using observational data and applying it in 2 programs, namely the Fast Fourier Transform (FFT) and the Lomb Periodogram, it produces values that can be graphed for the spectrum of each of the 5 rain station areas, namely Jepara Lake, Labuhan Ratu, Taman Negeri, Kota Raman and Sri Gading. From the results, it can be seen which areas are predominantly affected by El Nino and La Nina. Based on the results of the two programs, both show that the rain station in the Lake Jepara area experiences more dominant El Nino and La Nina influences. Keywords: El Nino, La Nina, rain station, rainfall, Fast Fourier Transform, Lomb Periodogram